CAHP‐210 dialyzer influence on intra‐dialytic vancomycin removal - Lucksiri, Aroonrut; Scott, Meri K.; Mueller, Bruce A.; Hamburger, Richard J.; Sowinski, Kevin M. (Nephrology, dialysis, transplantation, 2002)
Background. Vancomycin is often administered during the last hour of haemodialysis because it was not removed significantly by older hemodialyzers. However, newer higher permeability hemodialyzers remove vancomycin, although the amount removed varies considerably between dialyzers. The purpose of this study was to determine the apparent amount of vancomycin removed during the last hour of haemodialysis with a CAHP‐210 hemodialyzer. Methods. Eight subjects with end‐stage renal disease (ESRD) received i.v. vancomycin 15 mg/kg after their regular haemodialysis session ended. Serum samples for the determination of vancomycin concentrations were obtained serially for 44 h. After a 3‐week washout, the study was repeated with the vancomycin infused during the last hour of their regular haemodialysis session using a CAHP‐210 hemodialyzer. Vancomycin concentrations were determined by the Enzyme Multiplied Immunoassay Technique. Differential equations describing a two‐compartment open infusion model were fitted to the serum concentration vs time data and pharmacokinetic parameters and apparent vancomycin removal was estimated. Results. The median age and weight of the subjects were 52 years (range 37–71) and 75.6 kg (range 37.6–89.8), respectively. The apparent vancomycin intra‐dialytic removal was 0.24 (range −0.07–0.35), which was statistically significantly different from zero. Conclusions. Vancomycin administered during the last hour of CAHP‐210 dialysis results in 24% less vancomycin exposure than when administered post‐haemodialysis. This intra‐dialytic drug loss should be accounted for when dosing vancomycin in this manner.